2018
DOI: 10.1590/0103-1104201811803
|View full text |Cite
|
Sign up to set email alerts
|

Fragilidade na governança regional durante implementação da Rede de Urgência e Emergência em Região Metropolitana

Abstract: RESUMO Este artigo analisa a implementação da Rede de Urgência e Emergências, seus arranjos interfederativos regionais de pactuação e gestão de políticas, na Região Metropolitana de São Paulo, no período de 2011-2016. Considera-se implementação como um processo dinâmico da política, com interação, negociação e aprendizagem permanentes. Este é um estudo de caso, baseado na pesquisa qualitativa em saúde e nos estudos de avaliação de implementação de políticas, com 4 níveis de análise imbricados: desenho de imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 6 publications
0
6
0
20
Order By: Relevance
“…Another important aspect emerging from the research dialogues with the analysis of Jorge et al 3 , who states that the transfer of financial resources, by itself, did not guarantee the effectiveness of the networks, and that the implementation of the RUE was not accompanied by changes in the care model. In the same direction, Padilha et al 14 observed in the Metropolitan Region of São Paulo the absence of arrangements capable of involving and articulating in communicative action all those with power in the points of attention and management spaces of the RUE, ensuring permeability to services.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another important aspect emerging from the research dialogues with the analysis of Jorge et al 3 , who states that the transfer of financial resources, by itself, did not guarantee the effectiveness of the networks, and that the implementation of the RUE was not accompanied by changes in the care model. In the same direction, Padilha et al 14 observed in the Metropolitan Region of São Paulo the absence of arrangements capable of involving and articulating in communicative action all those with power in the points of attention and management spaces of the RUE, ensuring permeability to services.…”
Section: Discussionmentioning
confidence: 90%
“…To Moreira et al 21 , the political system and the state executive power are the major absentees in the coalitions supporting SUS regionalization policies. Padilha et al 14 observed asymmetrical power relations that generate litigation, such as federal underfunding, non-state co-financing, the fragility of cooperative agreement instruments and competition between federal entities and their service networks. Regarding the action of the state entity in the construction of regional networks, studies have reported the insufficient coordination of state governments 3, 19 , often restricted to their role as managers of the services themselves 22 .…”
Section: Reflections and Contingencies Of Management Movements In Net...mentioning
confidence: 99%
“…Outro aspecto importante que emergiu da pesquisa dialoga com a análise de Jorge et al 3 , de que o repasse de recursos financeiros, por si só, não garantiu a efetivação das redes e que a implantação da RUE não se fez acompanhada de mudanças do modelo assistencial. Nessa mesma direção, Padilha et al 14 observaram na Região Metropolitana de São Paulo a ausência de arranjos capazes de envolver e articular em ação comunicativa todos aqueles com exercício de poder nos pontos de atenção e espaços de gestão da RUE, garantindo permeabilidade aos serviços.…”
Section: Discussionunclassified
“…Sob esse ponto de vista, de análise do sistema de saúde pública e o trabalho em rede, o estudo A10 corrobora os estudos mencionados anteriormente, quando diz que a construção da rede de U/E, se constitui um desafio, pela complexidade e multiplicidade de pontos de atenção, tecnologias envolvidas e políticas fragmentadas aquém da sua importância para a saúde pública. Contudo, deve-se unir forças para integrar um sistema que durante muito tempo sofreu com a fragmentação, desarticulação e pouca cooperação dos municípios, regiões e estados brasileiros (Padilha et al, 2018).…”
Section: Fragilidades Da Aps No Atendimento a Necessidades Da Criançaunclassified